If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -1 = 12x + 3 Combine like terms: 16 + -1 = 15 15 = 12x + 3 Reorder the terms: 15 = 3 + 12x Solving 15 = 3 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 15 + -12x = 3 + 12x + -12x Combine like terms: 12x + -12x = 0 15 + -12x = 3 + 0 15 + -12x = 3 Add '-15' to each side of the equation. 15 + -15 + -12x = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -12x = 3 + -15 -12x = 3 + -15 Combine like terms: 3 + -15 = -12 -12x = -12 Divide each side by '-12'. x = 1 Simplifying x = 1
| x+6y=4v | | -5+-39x+8x^2=0 | | 8s-6=-13+9s | | 9p-24=0+p | | 3.25s=-29.25 | | 0.47-1.56= | | 6.25s=-37.5 | | x^2=12+3x | | -5x-12x=-119 | | 49=6x+7 | | 7x+7x=98 | | 3x-5+4x=9 | | -4x-18=-94 | | 57=3x | | 7x-4=2x*26 | | 9+3n=21 | | 2x-41=17 | | 9x-74=11x | | 525=900-300p | | (-3-1x)(1-2x)(x+3)= | | y=7x^2+21x-2 | | 8.25w=-74.25 | | -8+Y=-29 | | Z+13=-5 | | 9.25m=-74 | | A+13=-15 | | z+13=-15 | | w-15=19 | | 3x-1=a | | 100=(12x+8)-(4x+4) | | 50=(12x+8)-(4x+4) | | 87-6x=12x+19 |